Respuesta :

Simplifying K(t) = 13t + -2 Multiply K * t tK = 13t + -2 Reorder the terms: tK = -2 + 13t Solving tK = -2 + 13t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13t' to each side of the equation. -13t + tK = -2 + 13t + -13t Combine like terms: 13t + -13t = 0 -13t + tK = -2 + 0 -13t + tK = -2 Reorder the terms: 2 + -13t + tK = -2 + 2 Combine like terms: -2 + 2 = 0 2 + -13t + tK = 0 The solution to this equation could not be determined.